A self-consistent plasticity theory for modeling the thermo-mechanical properties of irradiated FCC metallic polycrystals. (May 2015) - Xiao, Xiazi; Song, Dingkun; Xue, Jianming; Chu, Haijian; Duan, Huiling
Abstract: A self-consistent theoretical framework is developed to model the thermo-mechanical behaviors of irradiated face-centered cubic (FCC) polycrystalline metals at low to intermediate homologous temperatures. In this model, both irradiation and temperature effects are considered at the grain level with the assist of a tensorial plasticity crystal model, and the elastic-visocoplastic self-consistent method is applied for the scale transition from individual grains to macroscopic polycrystals. The proposed theory is applied to analyze the mechanical behaviors of irradiated FCC copper. It is found that: (1) the numerical results match well with experimental data, which includes the comparison of results for single crystals under the load in different directions, and for polycrystals with the influences of irradiation and temperature. Therefore, the feasibility and accuracy of the present model are well demonstrated. (2) The main irradiation effects including irradiation hardening, post-yield softening, strain-hardening coefficient (SHC) dropping and the non-zero stress offset are all captured by the proposed model. (3) The increase of temperature results in the decrease of yield strength and SHC. The former is attributed to the weakened dislocation–defect interaction, while the latter is due to the temperature-strengthened dynamic recovery of dislocations through the thermally activated mechanism. The present model may provide a theoretical guide to predict the thermo-mechanical behaviors of irradiated FCC metals for the selection of structural materials in nuclear equipment. Abstract : Highlights: A tensorial plasticity crystal model with both irradiation and temperature effects is proposed. The thermo-mechanical behaviors of irradiated polycrystals have been obtained by using the elastic-visocoplastic selfconsistent method. The main characteristics of irradiated polycrystalline metals with temperature effect can be captured by the proposed model. The numerical results match well with corresponding experimental data.